Biết \(\displaystyle\int\limits_0^1\dfrac{dx}{\sqrt{x+1}+\sqrt{x}}=\dfrac{2}{3}\left(\sqrt{a}-b\right)\) với \(a,\,b\) là các số nguyên dương. Tính \(T=a+b\).
\(T=7\) | |
\(T=10\) | |
\(T=6\) | |
\(T=8\) |
Chọn phương án B.
Đặt $A=\displaystyle\int\limits_0^1\dfrac{dx}{\sqrt{x+1}+\sqrt{x}}$ ta có $$A=\dfrac{2}{3}\left(\sqrt{a}-b\right)\Leftrightarrow b=\sqrt{a}-\dfrac{3}{2}A.$$
Vì $a,\,b$ nguyên dương nên ta khảo sát hàm số $f(x)=\sqrt{x}-\dfrac{3}{2}A$ với $x\in\mathbb{Z}^+$ bằng chức năng TABLE trên máy tính cầm tay.
Vậy $a=x=8$ và $b=f(x)=2$. Do đó $a+b=10$.
Chọn phương án B.
\(\begin{eqnarray*}
&I&=\displaystyle\int\limits_0^1 \dfrac{\mathrm{\,d}x}{\sqrt{x+1}+\sqrt{x}}\\
&&=\displaystyle\int\limits_0^1\dfrac{\sqrt{x+1}-\sqrt{x}}{\left(\sqrt{x+1}+\sqrt{x}\right)\left(\sqrt{x+1}-\sqrt{x}\right)}\mathrm{\,d}x\\
&&=\displaystyle\int\limits_0^1\dfrac{\sqrt{x+1}-\sqrt{x}}{(x+1)-x}\mathrm{\,d}x\\
&&=\displaystyle\int\limits_0^1\left(\sqrt{x+1}-\sqrt{x}\right)\mathrm{\,d}x\\
&&=\displaystyle\int\limits_0^1\left((x+1)^{\frac{1}{2}}-x^{\frac{1}{2}}\right)\mathrm{\,d}x\\
&&=\left[\dfrac{2}{3}(x+1)^{\frac{3}{2}}-\dfrac{2}{3}x^{\frac{3}{2}}\right]\bigg|_0^1\\
&&=\dfrac{2}{3}\left[\sqrt{(x+1)^3}-\sqrt{x^3}\right]\bigg|_0^1\\
&&=\dfrac{4}{3}\left(\sqrt{2}-1\right)\\
&&=\dfrac{2}{3}\left(2\sqrt{2}-2\right)\\
&&=\dfrac{2}{3}\left(\sqrt{8}-2\right).\end{eqnarray*}\)
Theo đó \(a=8,\,b=2\).
Suy ra \(T=a+b=8+2=10\).